P3.284 Factors Associated with Variations in Culture Confirmation For Neisseria Gonorrhoea: A Study of Patients Attending Five Genitourinary Medicine Clinics in England. (13th July 2013) - Mohammed, H; Obi, C; Bignell, C; Dean, G; Hay, P; Robinson, A; Ross, J D C; Chisholm, S; Ison, C; Hughes, G
Abstract : Background: Screening for gonorrhoea at genitourinary medicine (GUM) clinics in England is routinely performed using Nucleic Acid Amplification Tests (NAATs), but confirmation of NAAT-positive specimens by culture is required to monitor trends in antimicrobial resistance for Neisseria gonorrhoeae. We determined the proportion of patients whose gonorrhoea diagnoses were confirmed by culture and investigated whether they differed from those that were only screened by NAATs. Methods: All NAAT-positive attendees reported to the GUM Clinic Activity Dataset (GUMCAD, a mandatory STI surveillance system among GUM clinics in England) from 5 clinics included in the Gonoccocal Resistance to Antimicrobial Surveillance Programme (GRASP) from July-September 2011 were included in this analysis. Data from both datasets were linked by patient episode; all NAAT-positive attendees that were matched to a record in GRASP were considered culture-confirmed. Patient characteristics that were significant on Pearson's chi-square were included in an age- and clinic-adjusted logistic regression model to determine adjusted odds ratios (aORs) for being culture-confirmed. Results: Among all 844 NAAT-positive attendees, 54% were culture-confirmed. Most attendees were between the ages of 15–34 years (70%), white (55%), and 52% of those who gave information on sexual orientation were men who had sex with men (MSM); 72% of symptomatic attendees were culture-confirmed (p < 0.001). Females and MSM were less likely than heterosexual males to be culture-confirmed [aOR(95% CI): 0.51(0.31–0.85), p = 0.010; and 0.49(0.30–0.80), p = 0.004, respectively], while those with a concurrent STI [1.69(1.15–2.49), p = 0.007], and those presenting with multiple infection sites [2.54(1.62–4.00), p < 0.001] were more likely to be culture-confirmed. Conclusion: Not all NAAT-positive attendees were culture-confirmed, but this may be because culture was either unsuccessful or not routinely performed among asymptomatic attendees. All NAAT-positive patients should be cultured before treatment, as routine culture confirmation is essential to ensure representative monitoring of trends in antimicrobial resistance to inform decisions regarding treatment guidelines for gonorrhoea.